Role of bilastine in allergic rhinitis: a review - Dhingra, Rachna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The prevalence of allergic diseases is increasing globally, most particularly in middle to low-income countries. Allergic rhinitis and urticaria are common allergic diseases that may have a major negative impact on patient’s quality of life. Bilastine, a novel new-generation antihistamine that is highly selective for the H1 histamine receptor, has a rapid onset and prolonged duration of action. In the fasting state bilastine is quickly absorbed, but the absorption is slowed when it is taken with food or fruit juice. Therefore, it is recommended that bilastine is taken at least one hour before and no sooner than two hours after a meal. This review article describes about the role of bilastine in allergic reactions.